(untitled) (Research, Society and Development, 2021)
Brazil has the largest vaccination program in the world, being recognized nationally and internationally. The National Immunization Program currently serves 212 million people. Created on September 18, 1973, it is a patrimony of the Brazilian state, maintained by the commitment and dedication of health professionals, managers and the entire population. In the face of the COVID-19 pandemic, nursing occupied the front line, in terms of visibility of its performance, dedication and competence. The result was the recognition of its importance beyond the walls of care environments. The objective of this study is to report the performance of the nursing team in the vaccination campaign against COVID-19 at a University Center. It is a descriptive study, with a qualitative approach, of the experience report type, which took place from the experience of nursing students and nurses. Considering the high number of elderly users to be immunized, these who, according to the Municipal Plan for Operationalization of Vaccination against COVID-19, are part of the target audience of the 1st phase of vaccination, it was necessary to have a proportion of nursing volunteers proportional user demand. Based on the above, the importance of the performance of the nursing team in the vaccine rooms is reiterated, and the extent to which these professionals are trained to work in the current pandemic scenario, even some still in academic life, the commitment and competence, which were acquired over years of study and learning.